Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Lizy

\(\left\{{}\begin{matrix}\dfrac{3}{\left|x+2\right|}+\dfrac{1}{\sqrt{y-2}}=4\\\dfrac{2}{\left|x+2\right|}-\dfrac{1}{\sqrt{y-2}}=1\end{matrix}\right.\)

Nguyễn Lê Phước Thịnh
24 tháng 1 2024 lúc 20:17

ĐKXĐ: x<>-2 và y>2

\(\left\{{}\begin{matrix}\dfrac{3}{\left|x+2\right|}+\dfrac{1}{\sqrt{y-2}}=4\\\dfrac{2}{\left|x+2\right|}-\dfrac{1}{\sqrt{y-2}}=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}\dfrac{3}{\left|x+2\right|}+\dfrac{1}{\sqrt{y-2}}+\dfrac{2}{\left|x+2\right|}-\dfrac{1}{\sqrt{y-2}}=5\\\dfrac{2}{\left|x+2\right|}-\dfrac{1}{\sqrt{y-2}}=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}\dfrac{5}{\left|x+2\right|}=5\\\dfrac{1}{\sqrt{y-2}}=\dfrac{2}{\left|x+2\right|}-1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}\left|x+2\right|=1\\\dfrac{1}{\sqrt{y-2}}=2-1=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x+2\in\left\{1;-1\right\}\\y-2=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x\in\left\{-1;-3\right\}\\y=3\end{matrix}\right.\left(nhận\right)\)

\(Đặt:\left\{{}\begin{matrix}a=\dfrac{1}{\left|x+2\right|}\left(x\ne-2\right)\\b=\dfrac{1}{\sqrt{y-2}}\left(y\ge2\right)\end{matrix}\right.\)

\(Có:\left\{{}\begin{matrix}\dfrac{3}{\left|x+2\right|}+\dfrac{1}{\sqrt{y-2}}=4\\\dfrac{2}{\left|x+2\right|}-\dfrac{1}{\sqrt{y-2}}=1\end{matrix}\right.\\ \Rightarrow\left\{{}\begin{matrix}3a+b=4\\2a-b=1\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}5a=5\\2a-b=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}a=1\\b=1\end{matrix}\right.\\ \Rightarrow\left\{{}\begin{matrix}\dfrac{1}{\left|x+2\right|}=1\\\dfrac{1}{\sqrt{y-2}}=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\left|x+2\right|=1\\\sqrt{y-2}=1\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}\left[{}\begin{matrix}x+2=1\\x+2=-1\end{matrix}\right.\\y-2=1^2=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\left[{}\begin{matrix}x=-1\left(TM\right)\\x=-3\left(TM\right)\end{matrix}\right.\\y=3\left(TM\right)\end{matrix}\right.\\ Vậy:\left(x;y\right)=\left\{\left(-1;3\right);\left(-3;3\right)\right\}\)


Các câu hỏi tương tự
Kim Tuyền
Xem chi tiết
Lizy
Xem chi tiết
mynameisbro
Xem chi tiết
ILoveMath
Xem chi tiết
Phạm Quang Minh
Xem chi tiết
Lizy
Xem chi tiết
ILoveMath
Xem chi tiết
Lizy
Xem chi tiết
Kiều Phương Phạm
Xem chi tiết